Pengaruh Disiplin Kerja dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada PT Galeri Print Indonesia - Sari, Ayu Purnama; Andara, Adissya Maya (Jurnal ATAMA, 2023)
The purpose of this study was to determine the effect of work discipline on employee performance, to determine the effect of work experience on employee performance and to determine the effect of work discipline and work experience on employee performance at PT Galeri Print Indonesia. This research uses a quantitative approach. The population in this study were 30 employees of PT Galeri Print Indonesia using the Saturated Sampling Technique, which is a sampling technique when all members of the population are used as samples so that the sample used in this study was 30 people. The results of this study obtained r table 0,374. The first hypothesis obtained results tcount > ttable (6,350 > 2,052) with a significant level <0,05 (sig. 0,000 > 0,05) then Ha is accepted. So that there is a significant influence between work discipline on employee performance at PT Galeri Print Indonesia. The second hypothesis is the result of tcount > ttable (5,237 > 2,052) with a level significant < 0,05 (sig. 0,000 > 0,05) then Ha is accepted. so that there is a significant influence between work experience on employee performance at PT Galeri Print Indonesia. The third hypothesis obtained the results of Fcount > Ftable (21.117 > 3.35) with a significant level of < 0,05 (sig. 0,000 > 0,05) so there is a significant influence of work discipline and work experience variables on employee performance at PT Galeri Print Indonesia. The conclusion from this study is that there is a significant influence between work discipline and work experience on the performance of employees of PT Galeri Print Indonesia.